Pengaruh Prevelensi Stunting Terhadap Indeks Pembangunan Manusia Di Sumatera Barat Tahun 2023 - Mexano Hans Gery (Jurnal Ekonomi dan Bisnis Digital, 2024)
This research aims to determine the effect of stunting prevalence on the human development index in West Sumatra. This research was motivated by the large number of stunting cases in West Sumatra, especially remote areas such as the Mentawai Islands Regency, which resulted in the prevalence of stunting increasing and affecting the Human Development Index in West Sumatra. This research uses a quantitative type of research using secondary data. This research carries out classical assumption tests, hypothesis testing using SPSS. Looking at the test results that have been carried out, it proves that the stunting prevalence variable has a significant effect on the Human Development Index (HDI), with a significant value of 0.003 < 0.05. The determination result obtained was 38.8%. This shows that the prevalence of stunting can predict information regarding the Human Development Index (HDI) 38.8% while the remaining 61.2% is influenced by other factors not included in this research.